2023
DOI: 10.3390/catal13020289
|View full text |Cite
|
Sign up to set email alerts
|

Lipase Production by Yarrowia lipolytica in Solid-State Fermentation Using Amazon Fruit By-Products and Soybean Meal as Substrate

Abstract: The production of polyunsaturated fatty acids from fish oil, which is related to various health benefits including effects against cardiovascular diseases, antihypertensive, anticancer, antioxidant, antidepression, anti-aging, and anti-arthritis effects, among others, can be advantageously performed through the application of lipase. However, the high cost associated with enzyme production can make the process unfeasible and thus alternative substrates should be investigated to solve these problems. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The physicochemical analysis of the raw materials revealed that feather meal and soy oil-cake had the highest protein content, with percentages of 91.32 % and 52.63 %, respectively ( Table 2 ). Soy oil-cake, a valuable vegetable-based protein source, has been recognized for its potential in supporting microorganism growth and facilitating efficient enzyme production [ 36 ]. Similarly, previous studies have highlighted the suitability of feather meal as a promising raw material for enzyme extraction [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical analysis of the raw materials revealed that feather meal and soy oil-cake had the highest protein content, with percentages of 91.32 % and 52.63 %, respectively ( Table 2 ). Soy oil-cake, a valuable vegetable-based protein source, has been recognized for its potential in supporting microorganism growth and facilitating efficient enzyme production [ 36 ]. Similarly, previous studies have highlighted the suitability of feather meal as a promising raw material for enzyme extraction [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Soybean oil-cake, characterized by its high protein content, serves as an abundant source of amino acids that can be effectively utilized by bacteria for efficient enzyme synthesis. Furthermore, soybean oil-cake encompasses a range of additional substances, including vitamins, sterols, pigments, and organic acids, which have the potential to further enhance the production of enzymes [ 36 ]. Similarly, although feather meal exhibits a lower protein content, it still provides essential amino acids and other essential components that effectively support the growth and metabolism of bacteria, enabling them to efficiently produce proteolytic enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the by-products, especially fibers, act as a physical support for microorganisms and reduce the cost of the culture medium. SSF allows the use of agro-industrial by-products as alternative substrates to reduce the environmental problems associated with inappropriate waste disposal [34].…”
Section: Characterization Of Cupuaçu Fat Cakementioning
confidence: 99%
“…Based on the information presented, the production of lipase can be stimulated by supplementing the culture medium, and adapting to the nutritional needs of the microorganism using different components and agro-industrial by-products. In addition, the use of by-products can emphasize the value of plant materials from specific regions, such as the Amazon region, by stimulating sustainable exploitation and contributing to the preservation of important biomes and the biotechnological production of materials with high added value [34,78,79].…”
Section: Optimization Of Lipase Production Using a Ccrd (2 3 )mentioning
confidence: 99%
See 1 more Smart Citation